AN ADULT CASE OF HENOCH-SCHÖNLEIN PURPURA WITH GASTROINTESTINAL AND RENAL INVOLVEMENT - Işılay Nadir; Saniye Topçu; Ece Kaptanoğlu (Archives of Rheumatology, 2003)
Henoch-Schönlein purpura is a small vessel vasculitis, commonly seen in children. Severe organ involvement is reported to be less than 2 %. Here we present an adult Henoch-Schönlein Purpura case with gastrointestinal and renal involvement.